EFECTO DE LA UTILIZACIÓN DE DIFERENTES SUSTRATOS COMPARTIMENTADOS POR NEURONAS Y ASTROCITOS, SOBRE LA CONCENTRACIÓN DE CALCIO EXTRA E INTRACELULAR (2003)
The substrate exchange mechanism between neurons and astrocytes is far from clear; even we do not acknowledge if the metabolic effects on host cells, are the result of calcium signaling. We expected that the neurons and astrocytes link up through calcium ncentrations, affect their metabolic functions. Calcium concentration was mmeasure through atomic absorption in the intra and extracellular media of primary cultures of astrocytes and neurones, and after one hour incubation with different substrates such as Iactate, glutamate, glutamine and acetate, at physiological concentrations. ANOVA and Duncan methods (p < 0.05) were used for the statistical analysis, using three replications with five repetitions. Results show that in vitro incubations with the different substrates cause variations in calcium concentration, of both media Cintra and extra). Certainly, metabolic stress also may influence such variations. In addition, astrocytes are less dependent on extracellular calcium than neurons. Differences in intracellular calcium concentrations, can increase cell metabolism, and raise up mitochondrial metabolism. It has been proposed that changes in calcium concentration affect cell metabolism in experiments in vitro, using different substrate